Studentsâ Mathematical Communication Ability and Self-Efficacy using Team Quiz Learning Model - Johar, Rahmah; Junita, Eka; Saminan, Saminan (Universitas Ahmad Dahlan, 2018)
This research aims to examine the improvement of mathematical communication skills of the students who learn using the team quiz learning model. This is an experimental research with pretest-posttest-control group design. The population of this study is all of the seventh-grade students in one of the junior high schools in Banda Aceh. We use a simple random sampling technique to obtain two classes as the research samples. The data were collected using tests of mathematical communication skills and self-efficacy questionnaires. The statistical tests used in this study were the paired t-test and two-way ANOVA. The results show that: (1) The improvement of the studentsâ mathematical communication ability in the team quiz class is higher than the conventional class; (2) The improvement of the studentsâ self-efficacy in team quiz class is higher than the conventional class; (3) There is no interaction between the learning model and the student level towards the students mathematical communication ability; and (4) There is no interaction between the learning model and the student level towards the studentsâ self-efficacy.